Localisation of Two Bioactive Labdane Diterpenoids in the Peltate Glandular Trichomes of Leonurus japonicus by Laser Microdissection Coupled with UPLC‐MS/MS. Issue 5 (9th May 2017) - Xiao, Chao‐Jiang; Liu, Yan‐Chun; Luo, Shi‐Hong; Hua, Juan; Liu, Yan; Li, Sheng‐Hong
Abstract: Introduction: Glandular trichomes of plants are biochemical factories that could produce, store and secrete copious pharmaceutically important natural products. The Labiatae plant Leonurus japonicus is an important traditional Chinese medicine used to treat gynecological diseases, and has abundant peltate glandular trichomes (PGTs), in which the secondary metabolites accumulated are still unknown. Objective: To study the secondary metabolites specifically accumulated in the PGTs of L. japonicus and their biological activities, and provide a new way to pinpoint bioactive natural products from plants. Methodology: Morphology of the trichomes on L. japonicus were observed under a scanning electron microscope. The PGTs of L. japonicus were precisely collected using laser microdissection (LMD) and analysed for their secondary metabolites with ultra performance liquid chromatography‐tandem mass spectrometry (UPLC‐MS/MS). Targeted compounds were isolated with classical phytochemical methods, and their structures were elucidated by spectroscopic analysis. Biological activities were evaluated by in vitro assays. Results: Two labdane diterpenoids, leoheterin (1) and galeopsin (2), were localised in the PGTs of L. japonicus . Antithrombotic activity of 1 in anti‐platelet aggregation assay induced by arachidonic acid was observed. Both compounds showed potential anti‐inflammatory activity by inhibiting proinflammatory cytokine TNF‐α. In addition, anti‐proliferative effect of both compounds on several cancer cell lines was also detected. Conclusion: Two bioactive labdane diterpenoids were localised in the PGTs of L. japonicus . The findings suggested that it might be an efficient approach to explore bioactive natural products from the glandular trichomes of medicinal plants with LMD‐UPLC/MS/MS. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Two labdane diterpenoids were localized in the peltate glandular trichomes of a Labiatae medicinal plant Leonurus japonicas using laser microdissection (LMD) in combination with UPLC‐MS/MS. Their anti‐platelet aggregation activity, anti‐inflammatory activity, and anti‐proliferative effect on several cancer cell lines were observed. The findings suggested an efficient approach to explore bioactive natural products from plant glandular trichomes with LMD‐UPLC/MS/MS.